‘Such a ceremonial perversion!’ baroque, capitalism, and a mouthful of birds - Beyad, Maryam Soltan; Rezaei, Tahereh (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
The baroque culture of the seventeenth century has considerable affinities with the culture industry of late capitalism. This paper focuses on Caryl Churchill and David Lan’s A Mouthful of Birds, premiered by Joint Stock at Repertory Theater in 1986, and tries to discover the baroque elements the play incorporates. This study is mainly concerned with the text of the play and does not deal with its performance or choreography. The writers aim to show that Churchill’s play is informed with baroque techniques, which although at times make compromise with the premises of capitalism, yet enhance its potential to criticize the culture industry of late capitalism.